Notch in memories: Points to remember. Issue 7 (15th April 2015) - Marathe, Swananda; Alberi, Lavinia
ABSTRACT Memory is a temporally evolving molecular and structural process, which involves changes from local synapses to complex neural networks. There is increasing evidence for an involvement of developmental pathways in regulating synaptic communication in the adult nervous system. Notch signaling has been implicated in memory formation in a variety of species. Nevertheless, the mechanism of Notch underlying memory consolidation remains poorly understood. In this commentary, besides offering an overview of the advances in the field of Notch in memory, we highlight some of the weaknesses of the studies and attempt to cast light on the apparent discrepancies on the role of Notch in memory. We believe that future studies, employing high‐throughput technologies and targeted Notch loss and gain of function animal models, will reveal the mechanisms of Notch dependent plasticity and resolve whether this signaling pathway is implicated in the cognitive deficit associated with dementia. © 2015 Wiley Periodicals, Inc.